Application Of The Cooperative Learning Method Supported By The Think-Pair-Share Strategy In Mathematical Concept Understanding - Al Ayyubi, Ibnu Imam; Apriyanti, Niken Siti Nur; Nurhikmah; Rahmawati, Siti (STIT Fatahillah, 2025)
This study aims to analyze the effectiveness of the cooperative learning method supported by the Think Pair Share (TPS) strategy in improving students' understanding of mathematical concepts, particularly at SDN Karangtanjung 2, with a population of all students at the school and a sample of 26 students from class V. This research uses a quantitative approach with a quasi-experimental method and non-random sampling technique. The instruments used are subjective tests that have been tested for validity and reliability. The data analysis prerequisite tests include descriptive statistics to provide an overview of the mathematics learning outcomes at each school, with mean and standard deviation values. The results of the study show a significant increase in the average score of students from 53.23 (pretest) to 74.27 (posttest), with a decrease in standard deviation, indicating improved homogeneity of results. The normality test shows that the data are normally distributed, while the paired sample t-test results (Sig. = 0.000) confirm a significant difference in students' abilities before and after the lesson. The TPS method allows students with varying levels of ability to support each other in understanding the material, thus improving learning outcomes uniformly. Therefore, this method can be recommended as an effective learning strategy to enhance students' understanding of mathematical concepts.